2021
DOI: 10.1051/ctv/ctv20213602126
|View full text |Cite
|
Sign up to set email alerts
|

Impact of trellis systems and rootstocks on global phenolic composition and antioxidant activity of ‘Isabel Precoce’ grapes produced during rainy seasons in semi-arid region of Brazil

Abstract: Crop components, such as trellis systems, might affect solar radiation uptake by grapevines while others, such as rootstocks, influence the vigor of the scion. Proper management provides a suitable reproductive and vegetative balance that could influence the chemical composition of grapes. This study aimed to characterize the global phenolic composition and antioxidant activity of ‘Isabel Precoce’ grapes raised for juice, growing under different trellis systems and rootstocks, in rainy seasons, in semi-Arid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Lower total polyphenols content and antioxidant activity were obtained with '101-14 Mgt' and 'IAC 572' rootstocks. Nevertheless, the amount and phenolic composition may vary according to different factors, such as grapevine variety, grape maturity, climate conditions, and exposure to ultraviolet light (Da Costa et al, 2021), and therefore its behavior over the years should be observed. Regarding the chromatic characteristics, differences were only observed for the Hue; higher values were related with '101-14 Mgt' and 'IAC 572' rootstocks (Table IV).…”
Section: Resultsmentioning
confidence: 99%
“…Lower total polyphenols content and antioxidant activity were obtained with '101-14 Mgt' and 'IAC 572' rootstocks. Nevertheless, the amount and phenolic composition may vary according to different factors, such as grapevine variety, grape maturity, climate conditions, and exposure to ultraviolet light (Da Costa et al, 2021), and therefore its behavior over the years should be observed. Regarding the chromatic characteristics, differences were only observed for the Hue; higher values were related with '101-14 Mgt' and 'IAC 572' rootstocks (Table IV).…”
Section: Resultsmentioning
confidence: 99%